Association of Use of Tourniquets During Total Knee Arthroplasty in the Elderly Patients With Post-operative Pain and Return to Function - Zhao, Jian; Dong, Xin; Zhang, Ziru; Gao, Quanyou; Zhang, Yunfei; Song, Junlei; Niu, Shun; Li, Tian; Chen, Jiying; Wei, Fei-Long (Frontiers in Public Health, 2022)
Objective: During total knee arthroplasty (TKA), tourniquet may negatively impact post-operative functional recovery. This study aimed at investigating the effects of tourniquet on pain and return to function. Methods: Pubmed, Embase, and Cochrane Library were comprehensively searched for randomized controlled trials (RCTs) published up to February 15th, 2020. Search terms included; total knee arthroplasty, tourniquet, and randomized controlled trial. RCTs evaluating the efficacies of tourniquet during and after operation were selected. Two reviewers independently extracted the data. Effect estimates with 95% CIs were pooled using the random-effects model. Dichotomous data were calculated as relative risks (RR) with 95% confidence intervals (CI). Mean differences (MD) with 95% CI were used to measure the impact of consecutive results. Primary outcomes were the range of motion (ROM) and visual analogue scale (VAS) pain scores. Results: Thirty-three RCTs involving a total of 2393 patients were included in this study. The mean age is 65.58 years old. Compared to no tourniquet group, the use of a tourniquet resulted in suppressed ROM on the 3rd post-operative day (MD, -4.67; [95% CI, -8.00 to -1.35]) and the 1st post-operative month (MD, -3.18; [95% CI, -5.92 to -0.44]). Pain increased significantly when using tourniquets on the third day after surgery (MD, 0.39; [95% CI, -0.19 to 0.59]). Moreover, tourniquets can reduce intra-operative blood loss (MD, -127.67; [95% CI, -186.83 to -68.50]), shorter operation time (MD, -3.73; [95% CI, -5.98 to -1.48]), lower transfusion rate (RR, 0.85; [95% CI, 0.73 to 1.00]), higher superficial wound infection rates (RR, 2.43; [95% CI, 1.04 to 5.67]) and higher all complication rates (RR, 1.98; [95% CI, 1.22 to 3.22]). Conclusion: Moderate certainty evidence shows that the use of a tourniquet was associated with an increased risk of higher superficial wound infection rates and all complication rates. Therefore, the findings did not support the routine use of a tourniquet during TKA.